The utility of cardiopulmonary exercise testing in athletes and physically active individuals with or without persistent symptoms after COVID-19 - Brito, Gisele Mendes; Prado, Danilo Marcelo Leite do; Rezende, Diego Augusto; de Matos, Luciana Diniz Nagem Janot; Loturco, Irineu; Vieira, Marcelo Luiz Campos; de Sá Pinto, Ana Lúcia; Alô, Rodrigo Otávio Bougleux; de Albuquerque, Lorena Christine Araújo; Bianchini, Flavia Riva; Pinto, Ana Jéssica; Roschel, Hamilton; et al. (Frontiers in Medicine, 2023)
Cardiopulmonary exercise testing (CPET) may capture potential impacts of COVID-19 during exercise. We described CPET data on athletes and physically active individuals with or without cardiorespiratory persistent symptoms. Participants’ assessment included medical history and physical examination, cardiac troponin T, resting electrocardiogram, spirometry and CPET. Persistent symptoms were defined as fatigue, dyspnea, chest pain, dizziness, tachycardia, and exertional intolerance persisting >2 months after COVID-19 diagnosis. A total of 46 participants were included; sixteen (34.8%) were asymptomatic and thirty participants (65.2%) reported persistent symptoms, with fatigue and dyspnea being the most reported ones (43.5 and 28.1%). There were a higher proportion of symptomatic participants with abnormal data for slope of pulmonary ventilation to carbon dioxide production (VE/VCO2 slope; p<0.001), end-tidal carbon dioxide pressure at rest (PETCO2 rest; p=0.007), PETCO2 max (p=0.009), and dysfunctional breathing (p=0.023) vs. asymptomatic ones. Rates of abnormalities in other CPET variables were comparable between asymptomatic and symptomatic participants. When assessing only elite and highly trained athletes, differences in the rate of abnormal findings between asymptomatic and symptomatic participants were no longer statistically significant, except for expiratory air flow-to-percent of tidal volume ratio (EFL/VT) (more frequent among asymptomatic participants) and dysfunctional breathing (p=0.008). A considerable proportion of consecutive athletes and physically active individuals presented with abnormalities on CPET after COVID-19, even those who had had no persistent cardiorespiratory symptomatology. However, the lack of control parameters (e.g., pre-infection data) or reference values for athletic populations preclude stablishing the causality between COVID-19 infection and CPET abnormalities as well as the clinical significance of these findings.